Proposed Strategy for PT Anugerah Pharmindo Lestari (APL) to Increase Merck Product Service Level (Case Study at Indomaret) - Abdullah, Rizal; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2015)
Abstract - PT. Anugerah Pharmindo Lestari (APL) is a national healthcare distributor appointed by PT. Merck Tbk as the main distributor in Indonesia. The company is responsible for distributing the entire Consumer Health products for all types of outlets, including minimarket Indomaret scattered throughout Indonesia.Based on the internal data of PT Merck, the service level of PT. APL to serve Indomaret below trading term agreement target, the average service level of PT APL in distributing the products of PT. Merck to Indomaret only 81%, far from the target of 100%, this final project intends to conduct an analysis of service level of PT. APL to Indomaret. Conceptual framework analysis of the final project is based on the concept of Service Quality Model and IPA Matrix. The final project will analyze the external and internal factors of the PT. APL, it will gain strengths and weaknesses of PT. APL in serving the needs of Indomaret. The next step is to conduct a survey to determine services quality dimensions of PT. APL which undervalued by Indomaret perspective as the customer. Indomaret satisfaction survey results along with the weaknesses of the internal analysis of PT. APL will become business issues to look for improvement strategies proposal.Based on the results of Indomaret satisfaction survey and IPA Matrix Model evaluation, PT. APL has a lower level of service quality on the dimensions of reliability and assurance. Based on internal and external analysis also indicates PT. APL have weaknesses in the delivery of goods to customers. Based on IPA Matrix result, PT. APL has four service parameters are in quadrant I (focus improvement), there are the delivery process that is not timely, error type of goods sent, error quantity of goods sent, and low capability of their KAM and Salesman.Improvement strategy proposal for PT. APL from the internal is the addition of fleet facilities, improvement of the ERP system which made a Merck products special code for Indomaret and automatic order input system, recruiting new KAM specifically serve and manage Indomaret, while the external side is a monthly regular meeting for coordination and evaluation of the service process between PT. APL, Indomaret, and PT. Merck as a principal.Keywords: Consumer Health, Service Level, Servqual Model, IPA Matrix ModelÂ